Kinetic Investigation of Degradation of 4-Nitrotoluene in Aqueous Environment by MnO2/Clinoptilolite/O3 Process - Shabnam Pourfalatoon (Archives of Hygiene Sciences, 2021)
Background & Aims of the Study: 4-Nitrotoluene (4NT) is a toxic, resistant, and carcinogenic pollutant. The current study aimed to investigate the degradation and mineralization of 4NT regarded as one of the components of petrochemical wastewater using MnO2/Clinoptilolite (CP)/O3 process. The present study also examined the effect of several operational parameters. Materials and Methods:  Synthesized wastewater was used in this study. It is proposed to apply a radical mechanism by the generation of an anion radical (   prior to hydroxyl radical in order to describe the interaction between ozone and MnO. Results: The obtained findings of the present study are not similar to those of the ozonation process alone. In ozonation, 4NT removal was positively affected by higher pH due to the formation of hydroxyl radicals. The degradation efficiency values of 4NT in optimum pH for the ozonation and MnO2/CP/O3 processes were reported as 89.0 and 98.5% within 75 min of reaction, respectively.